2018
DOI: 10.1039/c8tc04468f
|View full text |Cite
|
Sign up to set email alerts
|

Surface state modulation of red emitting carbon dots for white light-emitting diodes

Abstract: Clarifying the luminescence mechanism of nitrogen related surface states for carbon dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…Sun and et al [3] found that surface passivation by means of organic molecules provides stable surface energy traps that participate in the PL emission. The presence of different atoms at the surface, in particular different moieties of N, was shown to tune the emission properties of CDs [62,70,73], ascribing the blue emission to pyrrolic nitrogen, the green one to pyridinic nitrogen, and the red PL to the distortion of p-phenylenediamine [73]. Blue, green, and yellow emissions were related to surface states because of pH and solvent effects in CDs prepared via hydroquinone and EDA [31,74].…”
Section: The Surface Statesmentioning
confidence: 99%
“…Sun and et al [3] found that surface passivation by means of organic molecules provides stable surface energy traps that participate in the PL emission. The presence of different atoms at the surface, in particular different moieties of N, was shown to tune the emission properties of CDs [62,70,73], ascribing the blue emission to pyrrolic nitrogen, the green one to pyridinic nitrogen, and the red PL to the distortion of p-phenylenediamine [73]. Blue, green, and yellow emissions were related to surface states because of pH and solvent effects in CDs prepared via hydroquinone and EDA [31,74].…”
Section: The Surface Statesmentioning
confidence: 99%
“…Their concluding hypothesis states that imine groups on the surface of CDs creates surface defects which introduces energy levels into the bandgap of CDs, thus reducing the energy of the emitted PL. 126 Recently, Yuan et al 127 compared the optical and surface properties of 4 different CDs (figure 11a). The color of each CDs image in figure 11a represents the PL spectra of the produced CDs.…”
Section: Recent Developments In Understanding Carbon Dots Photoluminementioning
confidence: 99%
“…Some studies have shown a ratio between PL intensity and particle size, 2,18-22 surface states [1][2][3][23][24][25] and heteroatom (presence of oxygen, nitrogen or sulfur). 1,2,26,27 These properties can be dened during the synthesis process or through some type of treatment aer synthesis.…”
Section: Introductionmentioning
confidence: 99%